Effects of carbon nanotubes additions on flash ignition characteristics of Fe and Al nanoparticles. Issue 3 (4th March 2018) - Liu, Dong; Liu, Yanxiong; Liu, Guannan
ABSTRACT: The influences of carbon nanotubes (CNTs) additions on the flash ignition characteristics of Iron (Fe) and aluminum (Al) nanoparticles (NPs) were presented. CNTs can be used as the additive to these metal nanoparticles for improving the flash ignition and burning processes. Different mass fractions of CNTs additions were considered. The mixture of Al and CNTs could combust in air with obvious giant flame, whereas the mixture of Fe and CNTs combusted under a relative stable condition with slight red light. The temperature distributions were measured using non-contact optical method and showed that Al NPs mixed with CNTs were burning at a higher temperature level than Fe NPs. Although different mass fractions of CNTs cannot significantly change the overall flash ignition phenomenon, CNTs additions influenced the minimum ignition energy (MIE) of mixtures. The appropriate content of CNTs addition can decrease the Fe NPs MIE significantly. However, the Al NPs MIE decreased all along with the increase of CNTs content. The micro- and nano- structures of Fe and Al NPs with CNTs additions before and after ignitions were examined by scanning electron microscope and high-resolution transmission electron microscopy. It was found that the special thermal conductive characteristics of CNTs and the cross-connected features for metal particles with CNTs caused the enhancement of flash ignition.